Late Wisconsinan deglaciation and glacial lake development in the Appalachians of southeastern Québec - Parent, Michel; Occhietti, Serge (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1999)
Abstract Late Wisconsinan deglaciation in southeastern Québec was preceded by a northward ice-flow reversal that was recorded in the northeastern part of the region. The reversal event was generated by flow convergence toward the St. Lawrence Ice Stream, a northeastward-flowing ice stream which formed in the St. Lawrence estuary prior to 13 000 years BP and lasted until at least 12 400 years BP. In the Bois-Francs uplands, the flow reversal event led to the formation of a semi-detached ice mass that underwent widespread stagnation and downwasting. In the southwestern region, northward retreat of the margin of the Laurentide Ice Sheet was marked by the formation of a series of discontinuous recessional moraines and by the development of ice-dammed lakes in the main valleys. The level of these lakes fell as progressively lower outlets became ice-free. The main episodes are (1) the Sherbrooke Phase of Glacial Lake Memphremagog, (2) an unnamed transitional lake and (3) Glacial Lake Candona, a large lake which had expanded northeastward from the deglaciated regions of the Upper St. Lawrence (Lake Iroquois) and Ottawa valleys to the Lake Champlain (Glacial Lake Vermont) basin. As recorded by the Danville Varves, Lake Candona lasted about 100 years following deposition of the Ulverton-Tingwick Moraine. Subsequent ice retreat along the Appalachian piedmont led to final drainage of Lake Candona and allowed Champlain Sea waters to invade much of these glaciolacustrine terrains about 12 000 years BP. On the basis of the Danville Varves record, a regional rate of ice retreat of about 200 m·a -1 is inferred. The age of the earliest moraine, the Frontier Moraine, is thus about 12 550 years BP, while the ages of the subsequent Dixville, Cherry River-East-Angus, Mont Ham and Ulverton-Tingwick moraines are estimated at 12 500, 12 325, 12 200 et 12 100 years BP, respectively.